Chemistry Teachers Introduce High-School Students to Advanced Topics Using a Poster Exhibition of Contemporary Organic Chemistry - Blonder, Ron (2014)
The 21st century presents many challenges for chemistry educators. Chemistry as an evolving entity is not reflected in the existing high-school chemistry curriculum. The goal of the current study is to examine teachers’ perceptions regarding introducing advanced topics in chemistry for high-school students by using a poster exhibition of contemporary organic chemistry. Four different groups of chemistry teachers participated in the study. The groups differ in their Content Knowledge (CK), and their experience in using the poster exhibition. The poster exhibition served as an effective means of support for teachers when high-school students were introduced to contemporary chemistry topics. CK was found to be an important component that positively influences teachers’ self-efficacy for using the poster exhibition in their class. However, the teachers’ CK was insufficient; the feelings of ownership and mastery experience are also important influential components that should be considered.